Injuries to the Stomatognathic System in Brazilian Jiu-Jitsu Athletes - Macêdo-Filho, R. A. (Sci Rep, 2019)
As a contact sport, Brazilian jiu-jitsu requires the fighter to expose his/her stomatognathic system to the adversary, making him/her more susceptible to oral and maxillofacial injuries and disorders. The aim of the present study was to determine the prevalence of injuries and disorders of the stomatognathic system and associated factors among practitioners of Brazilian jiu-jitsu. A total of 179 athletes were interviewed and submitted to a physical examination. The majority was male, in the beginner category and had participated in competitions. Athletes with more experience had a higher frequency of orofacial injuries (PR = 1.77; 95% CI: 1.01–1.38), such as oral mucous lacerations and skin abrasions in the facial region, which mainly occurred during training sessions. A mouthguard is not mandatory for the sport and many athletes (both beginners and more experienced athletes) do not use one due to difficulty breathing with the device. A prefabricated (type II) mouthguard was the most common among the athletes who used this equipment, although it does not offer adequate protection. Athletes on more advanced levels wore mouthguards significantly more often (PR = 1.96; 95% CI: 1.11–2.45). In conclusion, more experienced jiu-jitsu athletes had a higher frequency of orofacial injuries, such as lacerations and abrasions, and are more likely to wear a mouthguard. However, longitudinal studies are needed in order to assess the possible causes and risks.